Targeted Metabolomics Reveals Abnormal Hepatic Energy Metabolism by Depletion of β-Carotene Oxygenase 2 in Mice. Issue 1 (December 2017) - Wu, Lei; Guo, Xin; Lyu, Yi; Clarke, Stephen; Lucas, Edralin; Smith, Brenda; Hildebrand, Deana; Wang, Weiqun; Medeiros, Denis; Shen, Xinchun; Lin, Dingbo
Abstract β-carotene oxygenase 2 (BCO2) is a carotenoid cleavage enzyme located in the inner mitochondrial membrane. Ablation of BCO2 impairs mitochondrial function leading to oxidative stress. Herein, we performed a targeted metabolomics study using ultrahigh performance liquid chromatography-tandem mass spectroscopy and gas chromatography-mass spectroscopy to discriminate global metabolites profiles in liver samples from six-week-old male BCO2 systemic knockout (KO), heterozygous (Het), and wild type (WT) mice fed a chow diet. Principal components analysis revealed distinct differences in metabolites in the livers of KO mice, compared to WT and Het mice. However, no marked difference was found in the metabolites of the Het mouse liver compared to the WT. We then conducted random forest analysis to classify the potential biomarkers to further elucidate the different metabolomics profiles. We found that systemic ablation of BCO2 led to perturbations in mitochondrial function and metabolism in the TCA cycle, amino acids, carnitine, lipids, and bile acids. In conclusion, BCO2 is essential to macronutrient and mitochondrial metabolism in the livers of mice. The ablation of BCO2 causes dysfunctional mitochondria and altered energy metabolism, which further leads to systemic oxidative stress and inflammation. A single functional copy of BCO2 largely rescues the hepatic metabolic homeostasis in mice.